THE EFFECT OF ONLINE LEARNING VIA MICROSOFT TEAMS ON STUDENTS’ LEARNING OUTCOMES IN THE REACTION RATE TOPIC AMONG GRADE XI SCIENCE STUDENTS OF SMA NEGERI 6 AMBON - Perulu, Beatrix S; Palisoa, Napsin; Mariwy, Abraham (Molluca Journal of Chemistry Education (MJoCE), 2025)
This study was conducted with the objective to find out the significant influence between learning daring using microsoft teams on the reaction rate material on the learning outcomes of class XI Science students at SMA Negeri 6 Ambon in the 2020/2021 school year. The population of this study were students of class XI IPA 2 and a sample of 16 people. Data collection techniques using interviews and questionnaires. The results showed that there was a significant influence between learning daring using microsoft teams on student learning outcomes. This is evidenced by the results of the regression equation Y = 10.857 + 0.315x. This means that if learning daring using microsoft teams is increased by 1 point, the learning outcomes will increase by 31.5%, which means H0 is rejected and H1 is accepted.